2017
DOI: 10.1111/jnc.13969
|View full text |Cite
|
Sign up to set email alerts
|

Atrophin protein RERE positively regulates Notch targets in the developing vertebrate spinal cord

Abstract: The Notch signaling pathway controls cell fate decision, proliferation, and other biological functions in both vertebrates and invertebrates. Precise regulation of the canonical Notch pathway ensures robustness of the signal throughout development and adult tissue homeostasis. Aberrant Notch signaling results in profound developmental defects and is linked to many human diseases. In this study, we identified the Atrophin family protein RERE (also called Atro2) as a positive regulator of Notch target Hes genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Furthermore, a recent report indicates that RERE and its Drosophila homolog associate with histone methyltransferases to regulate gene expression 25. MDD is a polygenic and multifactorial disease, and gene–environment interactions play a pivotal role in its pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent report indicates that RERE and its Drosophila homolog associate with histone methyltransferases to regulate gene expression 25. MDD is a polygenic and multifactorial disease, and gene–environment interactions play a pivotal role in its pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RERE has also been shown to stimulate Notch target gene expression, including the expression of Hes genes, by preventing degradation of the Notch intracellular domain (Wang, Gui, Rallo, Xu, & Matise, 2017). Similarly, CHD7 is required for the full induction of Hes5 in quiescent neural stem/progenitor cells and loss of CHD7 function leads to decreased expression of the Notch ligand JAG1 in the developing inner ear (Hurd, Micucci, Reamer, & Martin, 2012;Jones et al, 2015).…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Thus, RERE may play a pivotal role in normal brain development 31,32. In addition, a recent report indicated that RERE and its Drosophila homolog were associated with histone methyltransferases in the regulation of gene expression 33. Gene–environment interactions play an essential role in MDD pathogenesis, which is a polygenic and heterogeneous disease.…”
Section: Discussionmentioning
confidence: 99%